CAS-1, a C. elegans cyclase-associated protein, is required for sarcomeric actin assembly in striated muscle - Nomura, Kazumi (The Company of Biologists, 2012)
Assembly of contractile apparatuses in striated muscle requires precisely regulated reorganization of the actin cytoskeletal proteins into sarcomeric organization. Regulation of actin filament dynamics is one of the essential processes of myofibril assembly, but the mechanism of actin regulation in striated muscle is not clearly understood. Actin depolymerizing factor (ADF)/cofilin is a key enhancer of actin filament dynamics in striated muscle in both vertebrates and nematodes. Here, we report that CAS-1, a cyclase-associated protein in Caenorhabditis elegans, promotes ADF/cofilin-dependent actin filament turnover in vitro and is required for sarcomeric actin organization in striated muscle. CAS-1 is predominantly expressed in striated muscle from embryos to adults. In vitro, CAS-1 binds to actin monomers and enhances exchange of actin-bound ATP/ADP even in the presence of UNC-60B, a muscle-specific ADF/cofilin that inhibits the nucleotide exchange. As a result, CAS-1 and UNC-60B cooperatively enhance actin filament turnover. The two proteins also cooperate to shorten actin filaments. A cas-1 mutation is homozygous lethal with defects in sarcomeric actin organization. cas-1-mutant embryos and worms have aggregates of actin in muscle cells, and UNC-60B is mislocalized to the aggregates. These results provide genetic and biochemical evidence that cyclase-associated protein is a critical regulator of sarcomeric actin organization in striated muscle.